Autism Spectrum Disorders and Attention-Deficit/Hyperactivity Disorder: is there a role for microbiota in differential diagnosis? A comprehensive review - Ivan Miranda Ramos (2022)
The differential diagnosis between Autism Spectrum Disorder (ASD) and Attention-Deficit/Hyperactivity Disorder (ADHD) has always been a challenge. Insufficient diagnostic accuracy contributes to the difficulty to distinguish them associated with high comorbidity and similarity. Recently, there has been an increase in the number of scientific publications referring that the analysis of the bacterial content present in the gut, the microbiota, can be a fundamental diagnostic tool in neurodevelopmental disorders. The present review aims to confirm the presence of specific gut microbial communities in each of these pathologies, its relationship with disease symptoms and the role of microbiota in the differential diagnosis of ASD and ADHD. However, in ASD and ADHD it is clear that a relationship between each of the pathologies individually and the microbiota exists. These neurodevelopmental disorders have many symptoms in common, they can occur separately or as a co-morbidity of each other, and the means of diagnosis existing are all subjective (clinical criteria, scales, questionnaires, etc.) not allowing us to make an infallible diagnosis. Hence, in order to distinguish these pathologies, a more objective diagnostic criterion is needed, such as the analysis of the gut microbiota.